Critical incidents of outsourcing processes in pharmaceutical supply chain: A mixed-methods approach - Valentina Marinkovic; Ina Heine; Andrijana Milosevic Georgiev; Robert Schmitt (Journal of Industrial Engineering and Management (JIEM), 2020)
Purpose: In this paper, a practical framework is presented for the successful integration of buyers and contract organizations based on the Critical Incident Technique (CIT). Methodology: The initial pool of situations was developed inductively according to qualitative data provided by ten experts in the field of outsourcing in pharmaceutical supply chain. Another group of experts evaluated these situations with regard to their degree of realism as well as relevance and allocated them to the five constructs (1) employee competence, (2) management commitment, (3) communication between organizations, (4) organizational culture, and (5) regulatory framework. Findings: The findings of the study show that communication appears to be the most frequent reason while regulatory framework seems to be the last frequent reason for critical incidents during outsourcing. Contract giver and service provide show diverging perceptions about the situations' degree of realism and relevance. Analysis of the interrater agreement shows that the allocation to a single construct is a challenge due to the critical incidents' complexity and multidimensionality. Originality: The critical incidents database and the presented framework serve as preventive behavioral-based quality management for the pharmaceutical supply chain.
Keywords: 650; critical incident technique; outsourcing; quality management; risk analysis; supply chain management